A contextual, theoretical and empirical analysis of the uses of university degrees as symbolic capital in self-initiated expatriation. (2015) - Ryan, Jason; Silvanto, Sari; Ozkaya, H. Erkan
This paper explores how the internationalisation of universities is impacting the symbolic capital that self-initiated expatriates rely upon to find work abroad. It contributes to the body of knowledge on institutional factors that enable and constrain self-initiated expatriation. Following a review of the literature, the authors develop and examine four hypotheses related to (1) the degree of international orientation of universities, (2) the political and economic globalisation of the countries in which they are located and (3) their academic reputations. Three of the hypotheses are supported by the analysis; a fourth hypothesis is rejected but reveals that talented graduates from well-regarded universities in economically less globalised countries are in high demand from employers in economically more globalised countries. Location, academic reputation and the international orientation of a university are found to be important factors influencing how large international employers perceive and assess global universities as a source of employable talent.